Efectos del social media como herramienta publicitaria para el posicionamiento de la marca de zapatos sunshine en el público femenino de 15 a 24 años en la ciudad de Guayaquil - Montenegro Peñafiel, Josselin María (2016)
This research project is originally based on information on the brand awareness of Sunshine, online store selling shoes in the social network users and verify the effectiveness of the strategy implemented when to publicize their products through the social media, the way that this company has adopted as a means of communication with their target audience. For a more thorough survey of the strategy adopted by the company, it will be established as a research technique the survey. The result of this research will reveal whether the brand is present in the mind of the target group, either by purchasing the product, on the recommendation of third parties or advertising that the company has made in social networks…..